2022
DOI: 10.1039/d1em00383f
|View full text |Cite
|
Sign up to set email alerts
|

Causal discovery of drivers of surface ozone variability in Antarctica using a deep learning algorithm

Abstract: The discovery of causal structures behind a phenomenon under investigation has been at the heart of scientific inquiry since the beginning. Randomized control trials, the gold standard for causal analysis,...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The input type of the reduced function must match the output type of the map function: the Text type and the IntWritable type. In this case, the output type of reduce function is Text and IntWritable, the former type of time stamp, and the latter type of the highest feature data, where all feature data are traversed during the design and construction of Hadoop-based intrusion detection big data analysis, and each record is compared until the best feature data match is found [21].…”
Section: Big Data Storage For Intrusion Detection Based On Hadoopmentioning
confidence: 99%
“…The input type of the reduced function must match the output type of the map function: the Text type and the IntWritable type. In this case, the output type of reduce function is Text and IntWritable, the former type of time stamp, and the latter type of the highest feature data, where all feature data are traversed during the design and construction of Hadoop-based intrusion detection big data analysis, and each record is compared until the best feature data match is found [21].…”
Section: Big Data Storage For Intrusion Detection Based On Hadoopmentioning
confidence: 99%
“…The input type of the reduce function must match the output type of the map function: the Text type and the IntWritable type. In this case, the output type of reduce function is Text and IntWritable, the former type of time stamp and the latter type of highest feature data, where all feature data are traversed during the design and construction of hadoop-based intrusion detection big data analysis, and each record is compared until a best feature data match is found until [20].…”
Section: Big Data Storage For Intrusion Detection Based On Hadoopmentioning
confidence: 99%
“…Kumar et al [KKM22] used TCDF to analyse the surface ozone variability in Antarctica. They concluded that most of the discovered relationships were in line with domain knowledge.…”
Section: Impact and Applications Of Tcdfmentioning
confidence: 99%
“…They concluded that most of the discovered relationships were in line with domain knowledge. Compared to other causality methods, they "prefer links identified by TCDF as it can identify the directions and lags in all those cases apart from accounting for hidden confounders and non-linearity of the processes involved in the analysis" [KKM22]. Causal models constructed by causal discovery methods have also proved useful for feature selection to remove irrelevant or redundant input features [SLL+15].…”
Section: Impact and Applications Of Tcdfmentioning
confidence: 99%